First complete providencia rettgeri genome sequence, the NDM-1-producing clinical strain RB151 (2017)
Providencia rettgeri is an opportunistic bacterial pathogen of clinical significance due to its association with urinary tract infections and multidrug resistance. Here, we report the first complete genome sequence of P. rettgeri. The genome of strain RB151 consists of a 4.8-Mbp chromosome and a 108-kbp blaNDM-1-positive plasmid.